Case Report: Primary cardiac diffuse large B-cell lymphoma with sick sinus syndrome and literature review on disease management and therapeutic strategies - Xiaofen Qiu; Xiaofen Qiu; Li Zhang; Shaojun Zhou; Wenbin Qian; Wenbin Qian; Yun Liang; Huiqing Qiu; Xianggui Yuan (Frontiers in Oncology)
BackgroundPrimary cardiac diffuse large B-cell lymphoma (DLBCL) is a rare but clinically challenging extranodal lymphoma. Diagnosis and management are often complicated due to its nonspecific symptoms and rarity.Case ReportWe reported a case of a 73-year-old male who initially presented with chest pain, high fever, dizziness, and amaurosis. Preliminary diagnostic assessments suggested sick sinus syndrome, necessitating the implantation of a dual-chamber pacemaker, and revealed a large mass in the interatrial septum. An endomyocardial biopsy confirmed the diagnosis of primary cardiac DLBCL. Initial treatment with R-miniCHOP chemotherapy yielded a partial response. However, due to treatment-related complications (grade 4 neutropenia and pneumonia), a change in the therapeutic regimen to OR-GemOx chemotherapy was made, leading to complete remission. A year later, the patient experienced a relapse, requiring a salvage treatment of the Pola-BR chemotherapy regimen, which again resulted in complete remission. Additionally, this review examines an in-depth literature review on the management and therapeutic strategies for this entity, focusing on the treatment recommendations for relapse/refractory disease.ConclusionPrompt diagnosis and effective management are crucial in treating primary cardiac DLBCL. While the emergence of new drugs has improved the prognosis by offering higher efficacy and fewer side effects, clinicians should be vigilant about potential cardiotoxicities.